2015
DOI: 10.1371/journal.pone.0142482
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Promoters of the MMP-2 and TIMP-2 Genes Are Associated with Spontaneous Deep Intracerebral Hemorrhage in the Taiwan Population

Abstract: BackgroundSpontaneous intracerebral hemorrhage (ICH) is a devastating stroke subtype. Matrix metalloproteinases (MMPs) function in the degradation of extracellular matrix and the activities of MMPs are modulated by their endogenous inhibitors, tissue inhibitors of metalloproteinases (TIMPs). This study aimed to discuss relationship of MMP-2 and TIMP-2 to spontaneous deep ICH (SDICH) susceptibility and hematoma size.MethodsAssociations were tested by logistic regression and general linear models (GLM) where app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…By disrupting Sp1 binding site, 37 the C-to-T transition at position 2735 and 21306 in MMP2 promoter region induces low MMP2 enzyme expression in stromal and neoplastic cells. 31 This explains, in part, the beneficial effect of lower expression of T allele in reducing excessive degradation of fibrillation collagen 29 and other ECM components and thus development of breast cancer. 34,38 Neither rs243864 (-790 G/A) nor rs243866 (-1575 G/A) MMP2 variants was associated with breast cancer in Tunisians, as MAF distribution of both variants was comparable between breast cancer cases and control women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By disrupting Sp1 binding site, 37 the C-to-T transition at position 2735 and 21306 in MMP2 promoter region induces low MMP2 enzyme expression in stromal and neoplastic cells. 31 This explains, in part, the beneficial effect of lower expression of T allele in reducing excessive degradation of fibrillation collagen 29 and other ECM components and thus development of breast cancer. 34,38 Neither rs243864 (-790 G/A) nor rs243866 (-1575 G/A) MMP2 variants was associated with breast cancer in Tunisians, as MAF distribution of both variants was comparable between breast cancer cases and control women.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies proposed that genetic polymorphism in MMP2 promoter region control MMP2 expression 23,31 and that sustained increased MMP2 levels might render the carriers more susceptible and aggressive to tumorigenesis. In this context, we examined the relationship between breast cancer susceptibility and the presence of MMP2 (promoter) variants: rs243864 (2790 G/T), rs243865 (21306 C/T), rs243866 (21575 G/A), and rs2285053 (2735 C/T) as potential risk biomarkers of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…TIMP‐2, the main endogenous inhibitor of MMP‐2, is responsible for regulating the functions of MMPs . The MMP‐2/TIMP‐2 expression ratio is an important factor in certain nervous and vascular disorders . In our study, the TIMP‐2 (rs2277698) gene polymorphism was shown to be weakly associated with DAVF patients subgrouped by CVR grading ( P = 0.026; OR 3.0 [95% CI 1.1–8.2]).…”
Section: Discussionmentioning
confidence: 53%
“…Further, while an intronic polymorphism of TIMP-1 rs2070584 C allele is associated with ICH in Chinese male patients [34], C allele of rs4898 provides a protective effect on DICH risk in the elderly male group [13]. Additionally, although the TIMP-2 AA rs7503726 genotype increased the risk of developing ICH in a genetic recessive model conducted on the German population [35], it was considered a protective factor against DICH in elderly Taiwanese females [14]. The disparity between the two reports may be due to different minor allele frequency (MAF) (39.14% in the former and 49.7% in the latter), heterogeneity of phenotypes, and stratification of subgroups in the latter report.…”
Section: Common Genetic Predisposition Of Ichmentioning
confidence: 99%
“…Further, men have younger age of ICH than women among Asians [12]. Differences in the exposure to causal factors, the control of hypertension and cholesterol, and the anticoagulant and antiplatelet treatment for stroke between countries and genders explain an important portion of the variance observed in ICH incidence between ethnicities [10] and genders [13,14,15,16]. However, a significant part of this variation remains unexplained.…”
Section: Introductionmentioning
confidence: 99%